Relationship of Regional Government and Village Government Before and After the Effect of Law Number 6 of 2014 Concerning Villages - Prasetiawan, Andik; Muhibbin, Moh. (International Journal of Social Service and Research, 2024)
The relationship between local and village governments becomes uncertain and blurs from its essence. In addition to exercising the remaining authority of the Regional Government although not herarchically but formalistically, the existence of the Village as a legal community unit that has original autonomy based on the right of origin is not fully recognized. As a unitary state, Indonesia recognizes and respects the existence of villages and customary villages, which are referred to as "unity of customary law communities", as stated in the constitutional basis of the 1945 Constitution. Thus this study focuses on two problem formulations. First, how was the relationship between the Regional Government and Village Government before and after the enactment of Law No. 6 of 2014? Second, what are the problems faced before and after the enactment of Law No. 6 of 2014?, when viewed from the concept of Autonomy? This research is a normative legal research, by analyzing the applicable laws and regulations related to Regional Government and Village Government before and after the enactment of Law No. 6 of 2014. This research uses two approaches, namely the juridical-normative approach (statue approach), and then the historical approach (historical approach). From the results of this study, there are several conclusions between him: First, the relationship between Regional and Village Governments, especially in Law No. 22 of 1999, and Law No. 32 of 2004, is increasingly unclear and tends to be partial. Because basically Villages and Regions are sub-systems of the Government that have their own government. On the contrary, it is regulated in one law, so that the essence of the Village as a legal community unit becomes blurred. Second, the design of Law No. 6 of 2014 concerning Villages, according to the concept of autonomy. The existence of the village actually strengthens the unitary state system by respecting and acknowledging its existence. The existence of Villages and Customary Villages as a legal community unit, as well as Village autonomy have a constitutional basis. The position of the village is not as the lowest composition of the Government, but a sub-system of the Government. because the Village according to this Law is a merger of two important elements, namely self-local governing community and local self government which is run based on the principles of recognition and subsidiarity.